Seismic Evidence for Fluid‐Driven Pore Pressure Increase and Its Links With Induced Seismicity in the Xinfengjiang Reservoir, South China. Issue 3 (23rd March 2022) - Dong, Shixian; Li, Lun; Zhao, Lingfeng; Shen, Xuzhang; Wang, Wentian; Huang, He; Peng, Borui; Xu, Xiao; Gao, Rui
Abstract: Xinfengjiang Water Reservoir (XWR), located in the northeast of Guangdong Province, South China, has hosted a large number of earthquakes since its impoundment. In order to understand potential triggering mechanisms of the reservoir‐induced seismicity that could help assess seismic hazard to the Greater Bay Area, the most populated region in China, in this study, we construct a high‐resolution shear‐wave velocity model in shallow crust at depths from surface to ∼10 km based on a high‐density short‐period seismic array recently deployed surrounding the XWR using ambient noise tomography. We image a northwest‐southeast (NW‐SE)‐trending high‐velocity belt at depths of 2–6 km and a relatively low‐velocity channel (LVC) underlying the high‐velocity belt at a depth below 6 km under the XWR. The LVC seems to indicate the existence of a NW‐SE‐trending channel for water infiltration below 6 km under the XWR. Combined with spatiotemporal variation of focal‐depth and frequency of seismicity under the XWR over the past decade, we infer that a NW‐SE‐trending preexisting fault has reactivated due to pore pressure increase via water infiltration from the dam to a recently most active region, Xichang, northwest of XWR. This scenario could possibly explain the occurrence of increasing seismicity in northwest of XWR since 2012. This study highlights the seismic evidence for pore pressure increase due to water infiltration that triggers seismicity and further offers a reference for other forms of fluid‐driven seismicity worldwide. Plain Language Summary: Human activities could induce the occurrence of earthquakes by altering the stresses and strains within the Earth's crust. The reservoir‐induced seismicity can be relatively large compared to other types of human activities. However, an understanding of underlying triggering mechanisms of induced seismicity and associated material properties for individual reservoir remains limited. In this study, we construct a high‐resolution shear‐wave velocity model in shallow crust at depths from surface to ∼10 km based on a high‐density short‐period seismic array with totally 220 seismic stations recently deployed surrounding the Xinfengjiang Water Reservoir, South China, using ambient noise tomography. Our shallow crust image, together with spatiotemporal distribution of seismicity over the past decade, shows a low‐velocity channel at depths of 6–10 km under the reservoir that is interpreted to be caused by pore pressure increase via water infiltration. The pore pressure increase could explain the recently increasing seismicity at northwestern corner of the reservoir. This study highlights seismic evidence for pore pressure increase due to water infiltration that triggers seismicity and further offers a reference for other forms of fluid‐driven seismicity worldwide. Key Points: A high‐resolution Vs model in shallow crust is constructed based on a dense seismic array under the Xinfengjiang Reservoir, South China A northwest‐southeast trending preexisting fault is inferred to reactivate due to reservoir water infiltration Pore pressure increase via water infiltration is suggested to be responsible for recently increasing seismicity in the northwest of the reservoir